Characteristic of volcanic deposits in the southern part of Gunung Karang, Pandeglang - West Java - Abdurrokhim, Abdurrokhim; Ismawan, Ismawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2016)
In the southern part slope of Gunung Karang in Pandeglang, there are many well-outcrops of volcanic materials that developed during Quaternary. The deposits represent various lithofacies both vertically and laterally.In general the lithologic characteristics that are found in the study area can be grouped into three units, (1). Tertiary sedimentary rock, which is consists of tuffaceous mudstones interbedded with fine-grained tuffaceous sandstone and siltstone, (2) primary volcanic product consist of andesite lava flow, volcanic breccia/agglomerate, and pyroclastic rocks (ash tuff, lapilli tuff, bomb/block, and lapilli tuff breccia, and (3) secondary volcanic products, which is consisting of laharic breccia and coarse-grained thick-bedded sandstone.In general the deposits become younger to the top of topography (Gunung Karang), but locally the deposits are most likely overlapping each other’s.Keywords: Volcanic deposits, Gunung Karang